A Mn(II)-Catalyzed Tandem Oxidative Cleavage and Ammoxidation of Alcohols to Primary Amides - Zhao, Kaili; Xie, Fukai; Li, Dongmei; Gao, Shuang (Synlett, 2023)
The cleavage/functionalization of C–C bonds in alcohols has emerged as a robust tool for exploration of new conversion. Herein, a Mn(OAc)2-catalyzed oxidative cleavage/ammoxidation of a wide range of alcohols to amides has been developed. The practicality of this transformation was demonstrated by a scale-up experiment and an amidation of mixed alcohols in a one-pot fashion. Moreover, a plausible mechanism was proposed based on a series of control experiments.
Keywords: alcohols; amides; manganese catalysis; tandem reactions; C–C bond cleavage; ammoxidation